Three Australian Lepidosperma Labill. Species as sources of prenylated and oxyprenylated derivatives of piceatannol, resveratrol and pinosylvin: Melatoninergic binding and inhibition of quinone reductase 2. (November 2022) - Hamid, Kaiser; Tran, Van H.; Duke, Rujee K.; Duke, Colin C.
Abstract: Prenylated and hydroxyprenylated piceatannol, resveratrol and pinosylvin derivatives were isolated from resin produced by three Australian Lepidosperma Labill. Species (Cyperaceae). From L. congestum R.Br. one known compound, 3′, 5′- bis -prenyl- E -resveratrol, and five undescribed compounds were isolated, 3′- O -prenyl-5′-prenyl- E -piceatannol, 5′, 6′- bis -prenyl- E -piceatannol, 5′-prenyl- E -piceatannol, 3′, 5′- bis (3-hydroxy-3-methylbutyl)- E -resveratrol and 3′, 5′- bis - E -hydroxyprenyl- E -resveratrol. From L. gunnii Boeckeler one undescribed compound was isolated, 3′- E -hydroxyprenyl-5′- Z -hydroxyprenyl- E -resveratrol. From L. laterale R.Br. six undescribed compounds were isolated, 3- O -prenyl- E -pinosylvin, 3- O - Z -hydroxyprenyl- E -pinosylvin, 3′- Z -hydroxyprenyl- E -resveratrol, 3- O - Z -hydroxyprenyl- E -resveratrol, 3- O - Z -hydroxyprenyl-4′- O -methyl- E -resveratrol, and 3- O -prenyl-3′-δ, δ′-dihydroxyprenyl- E -resveratrol. Compounds, including a reference compound 3- O -prenyl-3′- O -methyl- E -piceatannol, were screened in an assay for melatoninergic binding to MT1 and MT2 receptors and binding to QR2/MT3 enzyme, and for inhibition of QR2/MT3 in a functional assay. Strong binding was observed for 3- O - Z -hydroxyprenyl- E -resveratrol with a K i of 0.022 nM and the strongest inhibition of QR2/MT3 observed was for the reference compound, 3- O -prenyl-3′- O -methyl- E -piceatannol, with an inhibition of 61% at 1 μM and 95% at 10 μM. The three most active binders and inhibitors of QR2/MT3 were found to have a common substructure corresponding to 3- O -prenylresveratrol. Graphical abstract: Plant constituents' SAR indicates a substructure for QR2/MT3 inhibition. Image 1 Highlights: Hydroxyprenylated resveratrols with uncommon combination of E and Z stereochemistry. Three low micromolar QR2/MT3 inhibitors with 3- O -prenylresveratrol substructure. A compound binding to QR2/MT3 enzyme with a picomolar Ki value. 12 compounds not previously described from resin of Lepidosperma sedge plants. 4 stilbenoids with Z -stereochemistry of hydroxyprenyl group from L. laterale .